Birokrasi, Perilaku, dan Budaya Organisasi dalam Pendidikan Islam - Ainur Rofiq (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2019)
In the educational institution, organization is very important to increase the process and function of education. The man who has much knowledge in the organization will make a wide knowledge and a strong personality. The main purpose of bureaucracy is to give service to the public easy and fluently. In the education perspective, bureaucracy has a high goal to increase educational quality easy. When the educational institution was able to good, the process and educational function make maximum. Behavior organization is a science that studies human behavior. It has a connection between human behavior and organization. the organizational culture and education have a relationship stronger. The educational concept has raised of human-level as high creature, which has the ability to create value and function of culture. The organizational culture can affect new positive things in education. It comes from outside interaction. So, it will be a new culture in education, especially to increase educational institution